Characterization of conjugal transfer functions of Agrobacterium tumefaciens Ti plasmid pTiC58. - von Bodman, S B (1989)
Physical characterization of 13 transposon Tn5 insertions within the agrocinopine-independent, transfer-constitutive Ti plasmid pTiC58Trac identified three separate loci essential for conjugation of this nopaline/agrocinopine A + B-type Ti plasmid. Complementation analysis with relevant subcloned DNAs indicated that the three physically separated blocks of conjugal genes constitute distinct complementation groups. Two independent Tn5 insertions within the wild-type, agrocinopine-dependent, repressed pTiC58 plasmid resulted in constitutive expression of conjugal transfer. These two insertions were physically indistinguishable and could not be complemented in trans. However, the Trac phenotype resulted when the Tn5-mutated fragment cointegrated into the wild-type Ti plasmid. While the spontaneous Trac mutant Ti plasmids were also derepressed for agrocinopine catabolism, those generated by Tn5 insertions remained inducible, indicating that this apparent cis-acting site is different from that affected in the spontaneous mutants. No chromosomal Tn5 insertion mutations were obtained that affected conjugal transfer. An octopine-type Ti plasmid, resident in different Agrobacterium tumefaciens chvB mutants, transferred at normal frequencies, demonstrating that this virulence locus affecting plant cell binding is not required for Ti plasmid conjugation. None of our conjugal mutants limited tumor development on Kalanchoe diagremontiana. Known lesions in pTiC58 vir loci had no effect on conjugal transfer of this Ti plasmid. These results show that pTiC58 Ti plasmid conjugal transfer occurs by functions independent of those required for transfer of DNA to plant cells.